2022
DOI: 10.1097/inf.0000000000003653
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Persistent Symptoms Following SARS-CoV-2 Infection by Antibody Status in Nonhospitalized Children and Adolescents

Abstract: Background: The prevalence of long-term symptoms of coronavirus disease 2019 (COVID-19) in nonhospitalized pediatric populations in the United States is not well described. The objective of this analysis was to examine the presence of persistent COVID symptoms in children by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody status. Methods: Data were collected between October 2020 and May 2022 from the Texas Coronavirus Antibody REsponse Survey, a statewide prospective population-based su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…27 A couple of adult studies have similarly identified a lower risk of developing PCC in adults infected with the Omicron variant compared to the delta variant. 28,29 In contrast, a prospective cohort study in Norway, found a similar risk of persistent post-Covid symptoms in adults infected with the delta as those infected with the omicron variant. 30 On the opposite, S. Morikota et al, 31 in Japan, did not find significant differences in the prevalence of post-COVID-19 condition between the Omicron and pre-omicron groups.…”
Section: Discussionmentioning
confidence: 93%
“…27 A couple of adult studies have similarly identified a lower risk of developing PCC in adults infected with the Omicron variant compared to the delta variant. 28,29 In contrast, a prospective cohort study in Norway, found a similar risk of persistent post-Covid symptoms in adults infected with the delta as those infected with the omicron variant. 30 On the opposite, S. Morikota et al, 31 in Japan, did not find significant differences in the prevalence of post-COVID-19 condition between the Omicron and pre-omicron groups.…”
Section: Discussionmentioning
confidence: 93%
“…There is only one other study that has addressed this issue in children. Messiah et al showed that patients who did not report vaccination information were six times more likely to develop PCC than those who were vaccinated (RR: 5.76; 95% CI: 1.18–28.06) [ 39 ]. Studies in adults have shown a stronger protective effect of vaccinations, suggesting that vaccination before SARS-CoV-2 infection could reduce, but not eliminate, the risk of PCC.…”
Section: Discussionmentioning
confidence: 99%
“…Female sex, older age, multiple symptoms during acute COVID-19 infection, longer hospital stays, and respiratory distress following acute COVID-19 were risk factors related to long COVID in children and adolescents [ 18 , 28 ]. Experiencing severe symptoms during the acute phase of infection, being unvaccinated for COVID-19, and a high body mass index (BMI) that is equal to or greater than the 85th percentile for age and sex, can also increase the risk of long-COVID in this group of patients [ 49 ]. Maddux et al [ 50 ] reported that patients under 21 years of age were more likely to experience long COVID symptoms at 2 to 4 months follow-up if they had pre-existing respiratory conditions or co-morbidities including MIS-C.…”
Section: Discussionmentioning
confidence: 99%